Common impairments of emotional facial expression recognition in schizophrenia across French and Japanese cultures - Okada, Takashi; Kubota, Yasutaka; Sato, Wataru; Murai, Toshiya; Pellion, Fréderic; Gorog, Françoise (Frontiers in Psychology, 2015)
To address whether the recognition of emotional facial expressions is impaired in schizophrenia across different cultures, patients with schizophrenia and age-matched normal controls in France and Japan were tested with a labeling task of emotional facial expressions and a matching task of unfamiliar faces. Schizophrenia patients in both France and Japan were less accurate in labeling fearful facial expressions. There was no correlation between the scores of facial emotion labeling and face matching. These results suggest that the impaired recognition of emotional facial expressions in schizophrenia is common across different cultures.